Closed infusion system: A multimedia learning object for nursing education (Revista Contexto & Educação, 2025)
The teaching-learning process is a constant challenge for teachers. The search and introduction of new learning strategies have been desired in order to provide a pedagogical practice within the reach of students, respecting their autonomy and promoting a quality education. This paper presents a multimedia Learning Object (LO), named Sistema de Infusão Fechado (SIF) in Portuguese, which permits the learning of part of the programmatic content about intravenous therapy, highlighting the importance of the closed infusion system in infusion therapies of the parenteral solutions of large volumes. In the construction process of this LO, firstly, we aimed to know its main features, which could make it be an effective tool in the teaching-learning process. Thus, we were supported by the Ausubel’s Theory of Meaningful Learning, in order to follow the facilitative programmatic principals of the meaningful learning, and by the Cognitive Theory of the Multimedia Learning, with its principals which has as objective to align the learning process with the human cognition, with decreasing of the cognitive load, facilitating the learning process.
Keywords: Learning Object; Cognitive Theory of the Multimedia Learning; Meaningful Learning; Closed Infusion System